2008
DOI: 10.3170/2008-7-18530
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of floristic diversity in urban areas as a basis for habitat management

Abstract: Questions: How can floristic diversity be evaluated in conser‐vation plans to identify sites of highest interest for biodiversity? What are the mechanisms influencing the distribution of species in human‐dominated environments? What are the best criteria to identify sites where active urban management is most likely to enhance floristic diversity? Location: The Hauts‐de‐Seine district bordering Paris, France. Methods: We described the floristic diversity in one of the most urbanized French districts through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 39 publications
1
18
0
3
Order By: Relevance
“…However it can be compared to studies with similar sampling effort as Thompson, Hodgson, Smith, Warren, and Gaston (2004) who, despite including bryophytes and small trees, observed 159 species (1.5 species/m 2 ) in 52 English lawns, while Stewart et al (2009) found only 127 herbaceous species (0.3 species/m 2 ) in 327 residential lawns in New Zealand. Lawns seem to be relatively poor when compared to other urban vegetal communities, like wastelands (Muratet, Machon, Jiguet, Moret, & Porcher, 2007); but due to their large cumulated surface and their high numbers in cities (Muratet et al, 2008), they could play an important role in the dynamics of urban vegetal communities (Wania, Kuhn, & Klotz, 2006). The lawns we studied had similar communities to temperate semi-natural grasslands.…”
Section: Lawn Characteristicsmentioning
confidence: 96%
See 2 more Smart Citations
“…However it can be compared to studies with similar sampling effort as Thompson, Hodgson, Smith, Warren, and Gaston (2004) who, despite including bryophytes and small trees, observed 159 species (1.5 species/m 2 ) in 52 English lawns, while Stewart et al (2009) found only 127 herbaceous species (0.3 species/m 2 ) in 327 residential lawns in New Zealand. Lawns seem to be relatively poor when compared to other urban vegetal communities, like wastelands (Muratet, Machon, Jiguet, Moret, & Porcher, 2007); but due to their large cumulated surface and their high numbers in cities (Muratet et al, 2008), they could play an important role in the dynamics of urban vegetal communities (Wania, Kuhn, & Klotz, 2006). The lawns we studied had similar communities to temperate semi-natural grasslands.…”
Section: Lawn Characteristicsmentioning
confidence: 96%
“…To characterize the urban environment around lawns we analyzed the Land Use Pattern (LUP, scale = 1:5000, IAURIF, 2003) within a 200 m buffer radius (previously identified as the best radius to detect the influence of urban activity on floristic diversity: Muratet et al, 2008). We calculated the proportion of area occupied by buildings (vs. unbuilt areas) in the 200 m radius around each lawn.…”
Section: Characteristics Of the Lawns And Their Surrounding Urbanizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This species is one of the ''100 of the world's worst invasive alien species'' (Lowe et al 2000) and is often considered a prominent disturbance by managers of urban green spaces and parks. We focused on urban wastelands, a habitat frequently colonised by R. japonica that plays a major role in urban biodiversity, since they are numerous and widespread, exhibiting the highest floristic richness of all urban plant communities (Muratet et al 2007(Muratet et al , 2008. In its introduced range, R. japonica has been shown to alter plant and invertebrate species diversity in natural riparian habitats (Gerber et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The large number of existing inventory data can however be exploited to address other conservation issues, e.g. to quantify floristic index over a homogeneous region (Muratet et al 2008).…”
Section: Resultsmentioning
confidence: 99%